2012
DOI: 10.15376/biores.7.4.5879-5893
|View full text |Cite
|
Sign up to set email alerts
|

Production and Antioxidant Activity of Intracellular Polysaccharide by Hypsizigus Marmoreus Sk-01

Abstract: The extraction parameters of intracellular polysaccharide (IPS) from Hypsizigus marmoreus SK-01 mycelia were optimized, and the antioxidant activities of IPS were investigated. The optimum conditions of IPS extraction were predicted to be: an ultrasonic treatment time of 618.07 s, an extraction temperature of 84.53 °C, a pH of 7.57, and an IPS yield of ca. 6.84%. The in vitro inhibition effects of IPS on hydroxyl, superoxide anion, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals were 52.63 ± 3.19%, 68.21 ± 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Among the various nutrient substances obtained from mushrooms, polysaccharides have been demonstrated to possess a diversity of useful biological properties including anti-oxidant, anti-tumor, anti-bacterial, anti-inflammatory, immunomodulatory, anti-hyperglycemic and anti-hypercholesterolemic activities 14 . In light of these scientific findings, many investigators have devoted themselves to assessing the anti-diabetic effects of polysaccharides from either the fruiting body or mycelia, such as Phellinus baumii 15 , and Catathelasma ventricosum 16 .…”
mentioning
confidence: 99%
“…Among the various nutrient substances obtained from mushrooms, polysaccharides have been demonstrated to possess a diversity of useful biological properties including anti-oxidant, anti-tumor, anti-bacterial, anti-inflammatory, immunomodulatory, anti-hyperglycemic and anti-hypercholesterolemic activities 14 . In light of these scientific findings, many investigators have devoted themselves to assessing the anti-diabetic effects of polysaccharides from either the fruiting body or mycelia, such as Phellinus baumii 15 , and Catathelasma ventricosum 16 .…”
mentioning
confidence: 99%
“…Phenols [88] and polysaccharides are the major bioactive components present in H. marmoreus that show the antioxidant activity by scavenging reactive oxygen species and strengthening its reducing power [55]. Liu et al investigated the intracellular polysaccharides of H. marmoreus and revealed that these polysaccharides can be utilized as an antioxidant agent that improves adaptive immune reactions [89].…”
Section: Hypsizigus Marmoreusmentioning
confidence: 99%
“…content where A is the absorbance of the sample and A 0 is the absorbance of TEP. The content of malondialdehyde (MDA) was determined according to the method of Liu et al 24 with some modification. The reaction mixture, comprising 0.5 mL of sample, 1.5 mL of distilled water and 2 mL of TBA (6 g L −1 ), was heated in boiling water for 15 min.…”
Section: Biochemical Parametersmentioning
confidence: 99%